Dichroic Circular Polarizers Based on Plasmonics for Polarization Imaging Applications - Junyan Zheng; Xin He; Paul Beckett; Xinjie Sun; Zixin Cai; Wenyi Zhang; Xu Liu; Xiang Hao (Nanomaterials, 2021)
Dichroic circular polarizers (DCP) represent an important group of optical filters that transfer only that part of the incident light with the desired polarization state and absorb the remainder. However, DCPs are usually bulky and exhibit significant optical loss. Moreover, the integration of these kinds of DCP devices can be difficult and costly as different compositions of chemicals are needed to achieve the desired polarization status. Circular polarizers based on metasurfaces require only thin films in the order of hundreds of nanometers but are limited by their sensitivity to angle of incidence. Furthermore, few existing solutions offer broadband operation in the visible range. By using computational simulations, this paper proposes and analyses a plasmonic DCP structure operating in the visible, from 400 nm to 700 nm which overcomes these drawbacks. The resulting circular dichroism transmission (CDT) is more than 0.9, and the maximum transmission efficiency is greater than 78% at visible wavelengths. These CDT characteristics are largely independent of angle of incidence up to angles of 80 degrees.